Spatial and seasonal salt translocation in the young soils at the coastal plains of the Caspian Sea. (20th July 2021) - Konyushkova, M.; Alavipanah, S.; Heidari, A.; Kozlov, D.; Yu, Meshalkina; Semenkov, I.
Abstract: The primary formation of soil spatial heterogeneity of young surfaces is not well studied. Along the coast of the Caspian Sea, due to the constant sea-level changes of this closed water basin, young soilscapes have formed in the last centuries. The variability and the spatial pattern of soil salinity were studied at two key sites located at the coast of Russia (northern Dagestan) and Iran (northern Golestan) at the same altitude of 25.5 m below sea level, or 2.5 m above the present-day level of the Caspian Sea. The age of surface deposits is 50–70 years old at the Iranian coast ( Gomishan-1 ) and 293 ± 13 years calBP at the Russian coast ( Caspii-2 ). The soils at both key sites are weakly developed strongly saline soils (Gleyic Solonchaks). The key sites have similar aridity and lithology with different vegetation and microtopography: the Gomishan-1 site has a smooth microtopography and homogeneous vegetation, and the Caspii-2 site has a pronounced microtopography and diverse vegetation. Approx. 60 boreholes at each site were sampled twice to the depth of 1 m in autumn 2017 and 0.5 m in spring 2018. The electrical conductivity (1:2.5) was measured in soil samples. At both key sites, the spatial and seasonal salt translocation is well pronounced. The variability of soil salinity grows by the end of the dry and hot season (September/October). The mean, median and variance differ between two sites in spring and become similar between two sites in autumn, which shows that the seasonal drying of coastal soils leads to the formation of similar heterogeneity under similar aridity and lithology despite the differences in vegetation and microtopography. Even with the strong seasonal dynamics at both key sites, there are clear trends in these changes, which show that the spatial pattern is stable in time. The analysis of the relationship between salinity patterns and vegetation has shown that there is no such correlation at both key sites. The analysis of the relationship between salinity patterns and microtopography has shown that there is no such correlation at the younger site ( Gomishan-1, Iran) and there is a moderate correlation at the more mature site ( Caspii-2, Russia ) where soil salinity is inversely dependent on the microtopography (R 2  = 0.21 … 0.46). The overview of the facts obtained in this study as well as in the published literature led us to the conclusion that the formation of spatial heterogeneity in soil salinity chronologically precedes the spatial distribution of vegetation and microtopography at the coastal area of the Caspian Sea.